Emodin Protects against High-Fat Diet-Induced Obesity via Regulation of AMP-Activated Protein Kinase Pathways in White Adipose Tissue - Tzeng, Thing-Fong; Lu, Hung-Jen; Liou, Shorong-Shii; Chang, Chia Ju; Liu, I-Min (Planta Medica, 2012)
Emodin is an active herbal component traditionally used in China for treating a variety of diseases. The aim of this study was to examine the effect of emodin on the reducing lipid accumulation in white adipose tissue of high-fat diet-fed rats, and on the regulation of the expression of the genes involved in lipid metabolism to elucidate the mechanisms. After being fed a high-fat diet for two weeks, rats were dosed orally with emodin (20, 40, 80 mg/kg/day) or pioglitazone (20 mg/kg/day), once daily for eight weeks. Changes in body weight, feeding pattern, serum lipids, coronary artery risk index, and atherogenic index were investigated. Subcutaneous white adipose tissues were isolated for pathology histology and Western blot analyses. Changes of triglyceride accumulation in differentiated 3 T3-L1 adipocytes were also investigated. Emodin exhibited a significant concentration-dependent decrease in the intracellular accumulation of triglyceride in 3 T3-L1 adipocytes. Emodin (80 mg/kg/day) displayed similar characteristics to pioglitazone (20 mg/kg/day) in reducing body weight gain and plasma lipid levels as well as the coronary artery risk and atherogenic indices of high-fat diet-fed rats. Emodin also caused dose related reductions in epididymal white adipose tissue sizes in high-fat diet-fed rats. Emodin and pioglitazone enhanced the phosphorylation of AMP-activated protein kinase and its primary downstream targeting enzyme, acetyl-CoA carboxylase, upregulated gene expression of carnitine palmitoyl transferase 1, and downregulated sterol regulatory element binding protein 1 and fatty acid synthase protein levels in the epididymal white adipose tissue of high-fat diet-fed rats. Our findings suggest that emodin could attenuate lipid accumulation in white adipose tissue through AMP-activated protein kinase activation.
Keywords: AMPK; emodin; high-fat diet; lipid; white adipose tissue